Russian syntax for students of “Foreign linguistics” department (Proceedings of Southern Federal University. Philology, 2015)
This article discusses the principles of formation of the course Russian syntax for the students of “Foreign linguistics” department considering application tasks and modern concepts of active teaching. It is demonstrated how without abandoning theoretical problematics and maintaining the necessary sections (syntax of words, sentences and text) within the course it is developed syntactic knowledge and skills necessary for teaching, translation, editing activities, creation and critique texts, advance in computer processing of language.Key words: Russian language, syntax of words, syntax of sentence, syntax of text, translation, editing, teaching Russian, education formation.Sidorova Marina Yurievna - Moscow state university of M.V. Lomonosov, professor of Russian language dpt., Ph.D. of linguistics, professor assistant. Тел.: +7-909-968-01-99; e-mail: sidorovadoma@mail.ru